Mast cells as important regulators in the development of psoriasis - Zhou, Xu-Yue; Chen, Kun; Zhang, Jia-An (Frontiers in Immunology, 2022)
Psoriasis is a chronic inflammatory immune skin disease mediated by genetic and environmental factors. As a bridge between innate and adaptive immunity, mast cells are involved in the initiation, development, and maintenance of psoriasis by interactions and communication with a variety of cells. The current review describes interactions of mast cells with T cells, Tregs, keratinocytes, adipocytes, and sensory neurons in psoriasis to emphasize the important role of mast cell-centered cell networks in psoriasis.